Pola Peresepan Anak dengan Infeksi Saluran Pernapasan Akut (ISPA) Non Pneumonia di Klinik - Handayani, Rini Sasanti; Sari, Ida Diana; Prihartini, Nita; Yuniar, Yuyun; Gitawati, Retno (Jurnal Kefarmasian Indonesia, 2021)
Acute respiratory infection (ARI) is a common disease in the community. Riskesdas 2018 stated that ARI prevalence was 4.4% and the highest was in 1-4 years old children (8%). The capitation payment system in clinics collaborated with BPJS Kesehatan demands the physician to prescribe as effective and as efficient as possible. On the other hand, the capitation tariff obtained by clinics is considered as too low, thus constrains of the prescription leading to irrational prescribing is likely to occur. This study analyses further the prescribing pattern for ARI children in clinics and its rationality based on the difference in source of funding. A cross sectional research using retrospective method was conducted. Data were gathered from 409 medical records and or patients’ prescription of children between 1-12 years old and diagnosed as having non pneumonia ARI during 1st January to 30th November 2019. Result showed that non pneumonia ARI patients were mostly boys (54,3%) aged 1-5 years old (6.0%). The average number of items for BPJS patients was 3,45, the percentage of generic prescribing was twofold higher for BPJS group (63.94%), the percentage of essential medicine prescribing was 63.96% while the percentage of antibiotic use was lower (48.50%). Dosage propriety for BPJS patients was 70.80% which was slightly higher than non-BPJS group. Overall, the prescribing indicators and dosage properness for BPJS patients were better than non-BPJS patients.